Determinants of Financial Stability of Islamic Insurance Companies Listed on Indonesia Financial Services Authority - Grandis Imama Hendra (Share: Jurnal Ekonomi dan Keuangan Islam, 2021)
Islamic insurance is an Islamic financial service that guarantees a participant's life, health, education, asset, and business. Some of them experienced a decline in their financial stability. This study aims to analyze the determinants of financial stability of Islamic insurance companies registered at the Indonesian Financial Services Authority (OJK) from 2014 to 2018. Thirty-eight data observations were acquired from eight full-fledged Islamic insurance businesses' financial reporting, analyzed using panel data regression. The dependent variable is financial stability, whilst investment, capital structure, insurance premiums, independent board of commissioners, sharia supervisory board, board of directors, and institutional ownership are the independent variables. The results show that financial stability is significantly affected by investment, insurance premiums, independent boards, and institutional ownership. The capital structure, sharia supervisory board, and board of directors do not affect the financial stability. Increasing the number of participant contributions and strategic investments should be a concern of Islamic insurance managers. The role of an independent board and Institutional owners supervisory could strengthen the financial stability of Islamic Insurance. Research on Financial stability is supporting the development of Islamic insurance companies.==================================================================================================== ABSTRAK – Determinan Stabilitas Keuangan Perusahaan Asuransi Syariah yang Terdaftar pada Otoritas Jasa Keuangan. Asuransi syariah adalah salah satu jasa keuangan Syariah untuk menjamin jiwa, kesehatan, pendidikan, aset dan bisnis. Beberapa perusahaan tersebut mengalami penurunan stabilitas keuangannya. Penelitian ini bertujuan untuk menganalisis determinan stabilitas keuangan perusahaan asuransi syariah yang terdaftar pada Otoritas Jasa Keuangan (OJK). Sebanyak 38 observasi diperoleh dari laporan keuangan 8 perusahaan asuransi syariah periode 2014-2018. Analisis dilakukan menggunakan regresi data panel. Variabel yang dipilih dalam penelitian ini adalah stabilitas keuangan sebagai variabel dependen, investasi, struktur modal, premi asuransi, dewan komisaris independen, dewan pengawas syariah, dewan direksi dan kepemilikan saham institusi. Hasil penelitian menunjukkan bahwa variabel investasi, premi asuransi, dewan komisaris independen dan kepemilikan saham institusi berpengaruh terhadap stabilitas keuangan perusahaan asuransi. Variabel struktur modal, dewan pengawas syariah dan dewan direksi tidak berpengaruh terhadap stabilitas keuangan. Peningkatan jumlah iuran peserta dan investasi strategis harus menjadi perhatian pengelola asuransi syariah. peran dewan independen dan pengawasan pemilik institusi dapat memperkuat stabilitas keuangan asuransi syariah. Penelitian stabilitas keuangan pada perusahaan asuransi memberikan dukungan terhadap pengembangan perusahaan asuransi syariah.